Logistical Reasons Causing Return from Retail: A Case of Pharmaceutical Retail Market in Pakistan - Shaiq, Dr. Mohammad; Alwi, Dr. S. Khurram Khan; Billo, Abdul Muqeet; Khan, Dr. Shahzada Azam; Tabassum, Dr. Saima (The journal of contemporary issues in business and government, 2021)
The main objective of the study was to identify the factors, especially related to logistics, that contribute the most to product returns from retail pharmacy market back to distributers and manufacturers. From literature search the mostly emphasized three logistical factors namely Customer Service (CS), Inventory and Storage (IS) and Transportation were picked to study their impact on Returns (RE). This study was conducted for the retail pharmacy market of Pakistan. Data was collected through a close ended questionnaire by a small team of enumerators. A total of 161 valid responses from a sample of 370 pharmacies, picked randomly, were received and analyzed through SPSS. The analysis indicated that CS and IS are significant contributors for the return of medicines (RE) from pharmacies to wholesalers or distributors. Role of TR was not very significant in the sample picked for this research.